Perceptions of Early Adolescents, Parents, Teachers, and Health Workers about Suicide in Early Adolescents - Atih Rahayuningsih; Achir Yani Syuhaemi Hamid; Budi Anna Keliat; Raden Irawati Ismail (GLOBAL HEALTH SCIENCE GROUP, 2022)
Suicide is a global problem. Every country has almost the same problems related to suicide, namely related to the statistical suicide rate which tends to increase, the increase in suicide as a cause of death, and the tendency to incidence of suicide at a younger age. This study purposes to explore the perceptions of early adolescents, parents, teachers, and health workers about suicide in early adolescents. The research method uses descriptive qualitative. The study obtained data from twenty-three participants. Determining participants by purposive sampling. Research sites for several junior high schools in Jakarta. Analyzing the interview transcript data using the Colaizzi method. Producing six themes covering perceptions of suicide risk, perceptions of causes of suicide risk, primary responses to stressors that cause suicide risk, assessment of coping sources in facing suicide risk, risk of suicide as a destructive coping mechanism, and strategies to prevent suicide risk in adolescents. early. The results of the study were recommended as variables in building a suicide prevention model in early adolescents.